2014
DOI: 10.1371/journal.pone.0091841
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Assessment of Mediterranean Marine Protected Areas Effects on Fish Assemblages

Abstract: Marine protected areas (MPAs) were acknowledged globally as effective tools to mitigate the threats to oceans caused by fishing. Several studies assessed the effectiveness of individual MPAs in protecting fish assemblages, but regional assessments of multiple MPAs are scarce. Moreover, empirical evidence on the role of MPAs in contrasting the propagation of non-indigenous-species (NIS) and thermophilic species (ThS) is missing. We simultaneously investigated here the role of MPAs in reversing the effects of ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
154
2
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(172 citation statements)
references
References 61 publications
13
154
2
1
Order By: Relevance
“…One reason for weaker and mixed outcomes in diversity is that not all species increase-and some decline-after reserve establishment (Micheli et al 2004b). As detailed in this section, community-level responses Variability in species diversity Decrease S: (Bates et al 2014) Variability/turnover in community assemblage/structure Lower S: (Fraschetti et al 2013, Mellin et al 2014, Wing & Jack 2013 Occurrence of nuisance species outbreaks Lower S: (McCook et al 2010) Resistance to disturbance Inconsistent or unaffected M: (Selig et al 2012, Worm et al 2006 Recovery rate Inconsistent or lower M: (Graham et al 2011, Worm et al 2006 Invasiveness Unaffected M: (Burfeind et al 2013, Guidetti et al 2014 a Increase can refer to a greater value (and decrease a smaller value) inside compared with outside reserves (more common) or after compared with before reserve establishment, depending on the study. b S, single study; M, meta-analysis, in which the response indicated is the cross-study average response, which might vary among studies.…”
Section: Community Consequences Of Marine Reservesmentioning
confidence: 99%
See 1 more Smart Citation
“…One reason for weaker and mixed outcomes in diversity is that not all species increase-and some decline-after reserve establishment (Micheli et al 2004b). As detailed in this section, community-level responses Variability in species diversity Decrease S: (Bates et al 2014) Variability/turnover in community assemblage/structure Lower S: (Fraschetti et al 2013, Mellin et al 2014, Wing & Jack 2013 Occurrence of nuisance species outbreaks Lower S: (McCook et al 2010) Resistance to disturbance Inconsistent or unaffected M: (Selig et al 2012, Worm et al 2006 Recovery rate Inconsistent or lower M: (Graham et al 2011, Worm et al 2006 Invasiveness Unaffected M: (Burfeind et al 2013, Guidetti et al 2014 a Increase can refer to a greater value (and decrease a smaller value) inside compared with outside reserves (more common) or after compared with before reserve establishment, depending on the study. b S, single study; M, meta-analysis, in which the response indicated is the cross-study average response, which might vary among studies.…”
Section: Community Consequences Of Marine Reservesmentioning
confidence: 99%
“…However, reserves might protect invasive species as well when targeted or susceptible to bycatch, harvested areas might provide source populations for nontarget invasive species that interact negatively with harvested native species [modeled by Kellner & Hastings (2009)], and increased tourism in reserves might enhance introductions of invasive species (Burfeind et al 2013). Although the balance of these factors that promote or impede invasiveness varies across locations, such that invasive species increase in some cases and decrease in others (Burfeind et al 2013), reserves typically have no effect on the presence of invasive species (Burfeind et al 2013, Guidetti et al 2014.…”
Section: Response To Heterogeneity In Space and Timementioning
confidence: 99%
“…The increase in density and mean size of individuals of overexploited species, along with recolonization of shallower habitats, are among the most evident and documented effects of protection within MPAs (La Côté et al, 2001;García-Charton et al, 2004;Claudet et al, 2006;Guidetti & Sala, 2007;Lester et al, 2009;Aburto-Oropeza et al, 2011;Guidetti et al, 2014;Hackradt et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, one study attributed the lower values within the MPAs to the restoration of predatory relationships (more and larger top predatorsgroupers-controlled the densities of lionfishes within the MPA; Mumby et al, 2011), whereas the other study attributed the lower densities to targeted removal (by spearfishing) within MPAs (Hackerott et al, 2013). Another study examining the effects of MPAs on alien fishes in the Mediterranean Sea, found that the density of alien species did not show any response to protection (Guidetti et al, 2014). Nevertheless, this study lacked appropriate impact assessment design that would allow pairwise comparisons of control and impact sites.…”
Section: Discussionmentioning
confidence: 99%